The Philosophy of Participation Management : Theoretical Reflections and Practical Relevance in Contemporary Organizations - Akh. Fawaid; Aisyah Asri Nurrahma (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The philosophy of management focuses on individual active involvement in decision-making and task implementation to create an inclusive and adaptive organization. This article explores participation management from a philosophical viewpoint, highlighting ethics and collective responsibility in management practice. Hence, the analysis shows that participation management can help an organization become more effective by strengthening communication, increasing a sense of ownership, and developing a collaborative work culture. Therefore, participation management also creates space for creativity and innovation when facing changes in the dynamic organizational environment. In conclusion, the integration of philosophy in participation management can ignite more humanistic, inclusive, and sustainability-oriented leadership practices. Participation management has emerged as a strategy to address complex challenges in today's organizational landscape.